ریاستِ مدینہ میں اقلیتوں کے حقوق: تجزیاتی مطالعہ: Rights of Minorities in the State of Medina: An Analytical Study - Dr Syed Iftikhar Ahmad; Dr shabir ahmad jamee; Najeebullah (International Research Journal of Arabic and Islamic Studies, 2024)
In the Islamic welfare state, Muslims and non-Muslims are equal in terms of rights. Just as the protection of the life, property, honor and dignity of a Muslim is the responsibility of the state, similarly, a non-Muslim citizen also has the right to protect his life, property, honor and dignity. The Islamic state not only allows all minorities to worship according to their faith, perform all rituals of marriage and death, but also protects them. Non-Muslim minorities have the legal right to live and do business in any part of the Islamic state. If someone harms their life, property, honor and dignity, the state is responsible for compensation.